Концепція формування системи управління якістю на промислових підприємствах - Лепа, В.В.; Грязєва, М.С. (Економіка промисловості, 2014)
Виділено теоретичні підґрунтя, методичні підходи та проблеми формування системи управління якістю. Досліджено процес управління якістю на підприємстві: виділено етапи управління, проаналізовано їх зміст і визначено методи управління якістю. Розроблено алгоритм формування системи управління якістю на промисловому підприємстві. Выделены теоретические основы, методы и проблемы формирования системы управления качеством. Исследован процесс управления качеством на предприятии: выделены этапы управления, проанализировано их содержание и методы управления качеством. Разработан алгоритм формирования системы управления качеством на промышленном предприятии. An unsatisfactory products and services quality of Ukrainian enterprises is a major cause of their low competitiveness. Implementation of the modern quality management system requires the development of corresponding concepts, i.e. the system for choosing the ways of solving the problem. The article highlights theoretical basis, methodological approaches and problems of forming a quality management system at the industrial enterprises of Ukraine. Structural analysis of the concept of "quality" has allowed identifying the main directions of improvement of quality management systems at industrial enterprises: identify components of quality control and factors that affect the quality, and offer quality indicators for individual components. In the article the process of quality management is studied including the allocated stages of management, analyzes of their contents, and determining the methods of quality management that should be applied to each of the selected stages. The theoretical generalization of components of quality mechanisms and methods of quality management has allowed developing an algorithm of forming a quality management system at an industrial enterprise. The proposed algorithm of forming a quality management system is universal and contains a series of sequentially combined mechanisms, models, and methods. Using the proposed mechanism the company’s management can determine the necessity of improvement or reforming of the existing system of quality, track the status of quality management, implement new approaches of quality management and determine their effectiveness. Developed theoretical and practical foundations of quality form the holistic concept of quality management system.